Utilization of Longan Leaves (Dimocarpus longan) Waste after Harvest for Silk Dyeing in Yu Wa Sub-District, Chiang Mai Province - Maha-in, Kongkiat; Mongkholrattanasit , Rattanaphol; Klaichoi, Charoon (Area Based Development Research Journal, 2020)
The elimination of longan leaves (Dimocarpus longan) waste after harvesting by disposal, recycling into fertilizer or burning is the cause of air pollution in the community. Therefore, this research took initiation in utilizing longan leaves waste after harvesting for silk dyeing under zero waste concept in Yu Wa sub-district, Chiang Mai province. The research method contains the following steps:1) studying problems and selecting the target area, 2) experimenting with dyeing and testing fabric dyed from longan leaves, 3) building the mutual understanding with the community, 4) brainstorming, analyzing and planning, and 5) disseminating knowledge. The experimental results from this study reveal that the extracted dye from longan leaves gives yellow to light brown color to silk fabrics. A comparison of pre-mordanting, mordanting and post-mordanting stages shows that post-mordanting gives the best results with stannous chloride, potassium aluminum sulphate and copper sulphate, yielding yellow to dark brown shades. However, ferrous sulphate gives out dark brown to black color shades. The tests of the color saturation to washing, abrasion, sweat, water and light reveal these properties at the high to highest level. The knowledge dissemination achieves the goal as the results indicate a very good level of local community members’ application of silk dyeing innovation to their career. During the brainstorming process for product development, a challenge was identified with low potentiality of product formation. To resolve this, the local products were then re-decorated in tie-dyed appearance. The concept of local product redesign and development rooting in local tradition was educated to the community. After knowledge dissemination, the community has established a group on longan-leaves-dyed fabric products, which generates an additional income of 2,500-3,000 baht per month. In conclusion, the awareness of environmental conservation has been significantly raised.